Accounting for Alcohol
1 online resource (308 pages)
Keywords: Consumption of alcohol is a globally ubiquitous, often controversial activity, and business organizations in this sector are of significant social and economic relevance. This book draws on accounting records from the sector to reveal fresh and unique insights into the historic development of the production of alcoholic beverages.Offering a historic overview of the three major areas of the alcohol industry – brewing, distilling and wine – this book reveals the commonalities and differences which are present in the industry, while also highlighting its social impact. The editors bring together contributions from around the world, including Mexico, France, Japan and Ireland, to demonstrate how accounting has developed over time. Offering diverse geographical and historical perspectives, it explores multiple aspects of accounting within the industry, including internal control, earnings management, competition, and regulatory aspects. The fascinating insights into breweries, wineries, spirit distillers, vineyards and other related organizations provides a unique historic perspective of accounting systems, techniques and practices.Drawing on an international range of examples and rich archival material, this valuable research collection will be of great interest to researchers and advanced students of accounting and business history.